The drafter [large type] - Harrison, Kim, 1966- (Harrison, Kim, 1966- Peri Reed chronicles., 2016)
"Detroit 2030. Double-crossed by the person she loved and betrayed by the covert government organization that trained her to use her body as a weapon, Peri Reed becomes a fugitive and joins forces with a mysterious rogue soldier in a deadly race to piece together the truth about her fateful final task"--